Temporal Variations of the Marine Geoid - Siegismund, F.; Köhl, A.; Rummel, R.; Stammer, D.; 1 Institute of Oceanography, Center for Earth System Research and Sustainability University of Hamburg Hamburg Germany; 2 Institute for Astronomical and Physical Geodesy Technical University of Munich Munich Germany (Journal of Geophysical Research: Oceans, 2020)
The effects of temporal changes in the marine geoid on estimates of the ocean dynamic topography are being investigated. Influences from mass redistribution due to changes of land hydrology, ice sheets, glacial isostatic adjustment (GIA), and ocean and atmospheric dynamics are considered, and the associated crustal deformation is included. The strongest signals are associated with the seasonal cycle caused by changes in terrestrial water storage and ice sheets as well as the redistribution of atmospheric mass. Second to this is the importance of an overall trend caused by GIA and decreasing ice sheets over Greenland and Antarctica. On long spatial scales, the amplitude of regional trends estimated for the geoid height has a sizable fraction of those from sea level anomaly (SLA) for the period 1993–2016, also after subtraction of steric height of the upper 1,000 m to analyze trends in deep ocean geostrophic currents. The estimated strong negative geoid height trend south of Greenland for the period 1993–2016 opposes changes in dynamic sea level for the same period thereby affecting past studies on changes of both the strength of the subpolar gyre based on SLA and the meridional overturning circulation on a section between Cape Farewell and Portugal applying ocean dynamic topography and hydrography. We conclude that temporal geoid height trends should be considered in studies of (multi)decadal trends in sea level and circulation on large spatial scales based on altimetry data referenced to a geoid field. Plain Language Summary: Changes in ocean surface currents are routinely obtained from satellite altimetry data. A correction for changes in the geoid, the equipotential surface of gravity closest to sea level, is considered small and thus usually neglected. We investigate temporal geoid height changes and potential implications on ocean circulation studies using space‐borne gravity data and results from ocean and atmosphere models to discover the individual processes of mass redistribution in the climate system ...